TRENDS IN ROMANIA'S ANIMAL PRODUCTION - Mircea Adrian GRIGORAS (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to analyze the trends in animal production in Romania and identify its position among the EU countries and make a few recommendations to improve the statement of the sector. Animal production declined both at the EU level and in Romania. The livestock decline in cattle and pigs resulted in meat and milk production as well as consumption declined. Poultry meat and mutton and goat meat as well as honey production increased. Food consumption and self sufficiency rate are still lower compared to the EU average and their level in the most important producing countries of products of animal origin. The achievements in animal production in Romania are below its potential to produce meat and milk and food security could not be assured to the population. A clear strategy and important measures are needed to increase milk and meat production: a higher forage production, a balanced feeding to animals, the use of high breeding value animals, the implementation of modern technologies, a high training level to farmers and units managers, a higher productivity and product quality, as well as farm competitiveness, creation of associative forms. A sustainable agriculture and mainly animal production could be developed only in intensive farm systems, but also in the mountain and hilly areas by small farms which could use the pastures and meadows. As a final conclusion, the future strategy must pay more attention to animal production and create a balance with crop production. Otherwise, Romania's agro-food market will always depend on imports, affecting local producers.